Cognitive Therapy and Logotherapy on Depression of Patients With Type 2 Diabetes Mellitus - Sutinah Sutinah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Diabetes mellitus (DM) is a severe health disorder that causes physical problems and psychosocial effects. Depression and anxiety are the most common psychosocial problems experienced by people with DM. The purpose of this study was to determine the impact of cognitive therapy and logotherapy on and anxiety in patients with Type 2 diabetes. Methods: A quasi-experimental design has been conducted for the study at a hospital in Jambi Province. The total sample of 90 respondents with a consecutive sampling method. The independent variables are cognitive therapy and logotherapy, while the dependent variables are depression and anxiety. Data were analyzed by paired sample t-test and ANOVA. Results: The results showed that cognitive therapy and logotherapy could reduce depression more than giving cognitive therapy alone with a p-value of 0.0005. Conclusions: Cognitive therapy and logotherapy can be standard therapy in dealing with patients with psychosocial problems.